2019
DOI: 10.1371/journal.pone.0210014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frontal-executive dysfunction on self-perceived hearing handicap in the elderly with mild cognitive impairment

Abstract: It is increasingly agreed upon that cognitive and audiological factors are associated with self-perceived hearing handicap in old adults. This study aimed to compare self-perceived hearing handicap among mild cognitive impairment (MCI) subgroups and a cognitively normal elderly (CNE) group and determine which factors (i.e., demographic, audiometric, or neuropsychological factors) are correlated with self-perceived hearing handicap in each group. A total of 46 MCI patients and 39 hearing threshold-matched CNE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Third, hearing and visual impairment may affect the perceiving and encoding of the test stimuli. It is likely that the measurement of memory can be influenced by sensory alterations, 64 a measurement error that should be assessed in future studies based on laboratory measurements. Having learning difficulties or being illiterate may also influence the cognitive test results.…”
Section: Study Limitations and Conclusionmentioning
confidence: 99%
“…Third, hearing and visual impairment may affect the perceiving and encoding of the test stimuli. It is likely that the measurement of memory can be influenced by sensory alterations, 64 a measurement error that should be assessed in future studies based on laboratory measurements. Having learning difficulties or being illiterate may also influence the cognitive test results.…”
Section: Study Limitations and Conclusionmentioning
confidence: 99%
“…Similarly, studies examining the relationship between attention and perception and HI, which are reported a decrease in attention and perception as the level of HI increases, also indicate a decrease in cognitive performance 9,17,18. Many studies have reported that auditory deprivation and social isolation affect cognitive performance by reducing the quality of communication, which in turn leads to depression and facilitates dementia 18–21. At the same time, limited cognitive skills increase the negative effects of HI and decrease auditory perception skills 12.…”
Section: Discussionmentioning
confidence: 98%
“…9,17,18 Many studies have reported that auditory deprivation and social isolation affect cognitive performance by reducing the quality of communication, which in turn leads to depression and facilitates dementia. [18][19][20][21] At the same time, limited cognitive skills increase the negative effects of HI and decrease auditory perception skills. 12 It is believed that increased hearing disability with age can cause neurodegenerative diseases, decreased cognitive skills, decreased auditory perception skills, and neurophysiological disorders, which negatively impact attention and memory skills.…”
Section: Discussionmentioning
confidence: 99%
“…Associations have been reported between hearing handicap and tinnitus distress (Henry, 2016;Ivansic et al, 2017); as the causal relationship between them is unknown, an association is specified. Executive function and hearing handicap share an association (Lee et al, 2019). Cuny et al (2004) have suggested that the laterality of a tinnitus percept may direct attention towards the tinnitus sound; however, executive functioning cannot cause tinnitus laterality, a causal relationship could be specified.…”
Section: Constructing Causal Models Of the Edmmentioning
confidence: 99%